Calcium Regulation on the Atrial Regional Difference of Collagen Production Activity in Atrial Fibrogenesis - Cheng-Chih Chung; Yung-Kuo Lin; Yao-Chang Chen; Yu-Hsun Kao; Yung-Hsin Yeh; Yi-Jen Chen (Biomedicines, 2021)
Background: Atrial fibrosis plays an important role in the genesis of heart failure and atrial fibrillation. The left atrium (LA) exhibits a higher level of fibrosis than the right atrium (RA) in heart failure and atrial arrhythmia. However, the mechanism for the high fibrogenic potential of the LA fibroblasts remains unclear. Calcium (Ca2+) signaling contributes to the pro-fibrotic activities of fibroblasts. This study investigated whether differences in Ca2+ homeostasis contribute to differential fibrogenesis in LA and RA fibroblasts. Methods: Ca2+ imaging, a patch clamp assay and Western blotting were performed in isolated rat LA and RA fibroblasts. Results: The LA fibroblasts exhibited a higher Ca2+ entry and gadolinium-sensitive current compared with the RA fibroblasts. The LA fibroblasts exhibited greater pro-collagen type I, type III, phosphorylated Ca2+/calmodulin-dependent protein kinase II (CaMKII), phosphorylated phospholipase C (PLC), stromal interaction molecule 1 (STIM1) and transient receptor potential canonical (TRPC) 3 protein expression compared with RA fibroblasts. In the presence of 1 mmol/L ethylene glycol tetra-acetic acid (EGTA, Ca2+ chelator), the LA fibroblasts had similar pro-collagen type I, type III and phosphorylated CaMKII expression compared with RA fibroblasts. Moreover, in the presence of KN93 (a CaMKII inhibitor, 10 μmol/L), the LA fibroblasts had similar pro-collagen type I and type III compared with RA fibroblasts. Conclusion: The discrepancy of phosphorylated PLC signaling and gadolinium-sensitive Ca2+ channels in LA and RA fibroblasts induces different levels of Ca2+ influx, phosphorylated CaMKII expression and collagen production.